Associations of child food insecurity in Florida with social determinants of health and child population health outcomes - Maxwell Droznin; Julia Fashner (Shahid Beheshti University of Medical Sciences, 2023)
Background: Child food insecurity (CFI) in Florida is 25% higher than the national average, however, no studies currently exist which investigate the association between CFI and population health or social determinants of health in the State. The goal of this study was to identify those variables in order to inform future policy addressing CFI in the state of Florida. Methods: Data on CFI, child health, and social determinants of health were collected from the Florida Department of Health website for the years 2014-2018. Variables were selected based on previous studies on CFI conducted primarily in the United States. A correlation analysis was conducted to determine associations between the selected variables and CFI in Florida. Results: CFI had a moderate positive association with emergency department visits among children aged 0-5 in the years 2017 and 2018. All other child health outcomes examined in this study did not have significant associations with CFI. Teenage mothers represented the strongest positive association with CFI whereas breastfeeding represented the strongest negative association.  Conclusion: In Florida, CFI surprisingly had few correlations with population health outcomes that have known national associations. This indicates that the factors contributing to and resulting from CFI are different in Florida relative to those found nationally. Several social determinants of health were identified that could help identify individuals and communities at increased odds of having CFI.